Choosing children genes, disability, and design - Glover, Jonathan (Oxford : Clarendon, 2006)
Genetic and reproductive technology offers us the possibility of choosing what kind of children we do and don't have. This book is written for anyone who is concerned about our human future.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Genetic disorders in children; Abnormalities, Human -- Genetic aspects; Genetic counseling; Human reproductive technology -- Moral and ethical aspects; Genetic engineering -- Moral and ethical aspects